Advances and Insights for Small Molecule Inhibition of Macrophage Migration Inhibitory Factor - Trivedi-Parmar, Vinay (J Med Chem, 2018)
Macrophage migration inhibitory factor (MIF) is an upstream regulator of the immune response whose dysregulation is tied to a broad spectrum of inflammatory and proliferative disorders. As its complex signaling pathways and pleiotropic nature have been elucidated, it has become an attractive target for drug discovery. Remarkably, MIF is both a cytokine and an enzyme that functions as a keto-enol tautomerase. Strategies including in silico modeling, virtual screening, high-throughput screening, and screening of anti-inflammatory natural products have led to a large and diverse catalog of MIF inhibitors as well as some understanding of the structure–activity relationships for compounds binding MIF’s tautomerase active site. With possible clinical trials of some MIF inhibitors on the horizon, it is an opportune time to review the literature to seek trends, address inconsistencies, and identify promising new avenues of research.